Pertanggungjawaban Pidana Dalam Delik Pencemaran Nama Baik Di Media Daring - Noval Dwi Satria; Gema Fajar Fitriansyah; Dwi Putri Lestarika; Ayu Putriyana (GLOBAL SCIENTS PUBLISHER, 2025)
The application of the ITE Law in defamation cases is closely related to how the state maintains a balance between protecting press freedom and respecting individual rights to a good name, with the creation of this scientific work which focuses on the discussion, How Press Freedom Affects Criminal Liability in Defamation Crimes in Online Media and Why the Application of the ITE Law Affects Reporting Accountability in Online Media which will later aim at studying how press freedom guaranteed by law in Indonesia, such as Law No. 40 of 1999 concerning the Press, affects criminal liability in defamation cases in online media, and how the limits of press freedom are applied in the digital space. This study uses a normative juridical method with a statutory and conceptual approach. The primary legal sources used are Law No. 40 of 1999 concerning the Press and Law No. 19 of 2016 concerning Information and Electronic Transactions (UU ITE). Freedom of the press plays a vital role in democracy, but in the context of online defamation crimes, limits must be applied to maintain a balance between freedom of expression and protection of an individual’s reputation. Law Number 40 of 1999 concerning the Press and Article 27 paragraph (3) of the ITE Law provide the legal framework governing these freedoms and limits.